Economic-digital profile of university students in times of COVID-19 - Zevallos Acosta , Uladislao (2021)
Objective. Describing the economic-digital profile of university students in times of COVID-19. Methods. The research had a quantitative approach of the basic type, observational-descriptive design and level; data were collected through a digital survey to know the variable of study in the students of the University of Huánuco during the period 2020. Results. The study included 11 000 (100 %) students, 58.7 % of whom were female, 81.7 % from the Huánuco campus, 43.4 % of whom were studying between the 5th and 8th cycles, and 25.3 % from the Law and Political Science academic program. Regarding digital resources, 46.8% use a laptop for their class sessions, 51.4% use a mobile Internet connection, 36.1% have normal bandwidth capacity (4M to 10M); 58% are located in the urban area, while 84.9% reported connectivity problems and the same percentage indicated that they use accessories for their classes. Regarding economic resources, the parents of 49.4 % of the students finance their studies, 89.9 % stated that the pandemic affected their economic income and 57.4 % consider that their educational continuity will be affected. Regarding the health situation, 71.7% are not in the group at risk of contracting COVID-19, 63.1% did not use discard tests, 62.3% said that some family member was infected and 9.3% of this group died. Conclusions. There is a complicated scenario for university students due to the presence of COVID-19 regarding digital, economic resources and the health situation that is impacting their professional training.